2016
DOI: 10.1038/cddiscovery.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Induction and inhibition of the pan-nuclear gamma-H2AX response in resting human peripheral blood lymphocytes after X-ray irradiation

Abstract: Human peripheral blood lymphocytes (HPBLs) are one of the most sensitive cells to ionizing radiation (IR) in the human body, and IR-induced DNA damage and functional impairment of HPBLs are the adverse consequences of IR accidents and major side effects of radiotherapy. Phosphorylated H2AX (γH2AX) is a sensitive marker for DNA double-strand breaks, but the role and regulation of the pan-nuclear γH2AX response in HPBLs after IR remain unclear. We herein demonstrated that the pan-nuclear γH2AX signals were incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 55 publications
4
41
0
Order By: Relevance
“…In agreement with these data, MLN4924-treatment of BV173 and SUPB15 cells resulted in increased nuclear γH2AX foci formation, which is an established marker of DNA damage (Figure 4(b)). In addition, a pan-nuclear γH2AX staining pattern was frequently observed in MLN4924-treated cells, which most likely represents apoptotic cells [51]. Consistently, a greater fraction of cells with >10 γH2AX foci in the nucleus were found in the presence of the pan-caspase inhibitor QVD-OPh (Figure 4(c)).…”
Section: Mln4924 Induces Dna Damage In Ph+ Leukemia Cell Linessupporting
confidence: 60%
“…In agreement with these data, MLN4924-treatment of BV173 and SUPB15 cells resulted in increased nuclear γH2AX foci formation, which is an established marker of DNA damage (Figure 4(b)). In addition, a pan-nuclear γH2AX staining pattern was frequently observed in MLN4924-treated cells, which most likely represents apoptotic cells [51]. Consistently, a greater fraction of cells with >10 γH2AX foci in the nucleus were found in the presence of the pan-caspase inhibitor QVD-OPh (Figure 4(c)).…”
Section: Mln4924 Induces Dna Damage In Ph+ Leukemia Cell Linessupporting
confidence: 60%
“…It has been reported that IR-induced pan-nuclear γ-H2AX response represents an apoptotic signal33343536. In the present study, we further observed that the pan-nuclear γ-H2AX response in HPBLs induced by α-particle irradiation from 241 Am source was co-localized with apoptotic TUNEL staining accompanying with γ-H2AX foci in neighboring cells; exposure to radon also induced the apoptotic pan-nuclear γ-H2AX response accompanying with intermittent linear γ-H2AX foci track and individual foci in neighboring cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by results from lymphocytes where numbers of γH2AX, phospho-ATM and phospho-DNA-PK foci were reduced by ca. 50-70% upon ATM inhibition [39].…”
Section: Discussionmentioning
confidence: 99%